(untitled) (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2025)
The problem of cerebral stroke remains of extreme social and medical importance throughout the world [1]. According to WHO, stroke is the leading cause of disability in the adult population. Violation of cerebral circulation is a concept that includes not only stroke, but also transitory cerebral circulation disturbances or transient ischemic attacks (TIA). Based on MRI data, it was found that at a TIA duration of more than 1 hour, persistent foci of ischemia appear in the brain. Therefore, at the suggestion of the World Stroke Organization, the diagnosis of TIA can be made only if the duration of symptoms does not exceed 60 minutes and is completely resolved. Otherwise, a diagnosis of stroke is made [2].